Mining Beneficial Genes for Aluminum Tolerance Within a Core Collection of Rice Landraces Through Genome-Wide Association Mapping With High Density SNPs From Specific-Locus Amplified Fragment Sequencing - Zhao, Minghui; Song, Jiayu; Wu, Aiting; Hu, Tao; Li, Jinquan (Frontiers in Plant Science, 2018)
Trivalent Aluminium (Al3+) in acidic soils is harmful to root growth and significantly reduce crop yields. Therefore, mining beneficial genes for Al tolerance is valuable for rice production. The objective of this research is to identify some beneficial genes for Al tolerance from rice landraces with high density SNP set from SLAF-seq (Specific-Locus Amplified Fragment sequencing). A total of 67,511 SNPs were obtained from SLAF-seq and used for genome-wide association study (GWAS) for Al tolerance with the 150 accessions of rice landraces in the Ting’s rice core collection. The results showed that rice landraces in the Ting’s rice core collection possessed a wide-range of variation for Al tolerance, measured by relative root elongation (RRE). With the mixed linear models, GWAS identified a total of 26 associations between SNPs and Al tolerant trait with p < 0.001 and false discovery rate (FDR) < 10%. The explained percentage by quantitative trait locus (QTL) to phenotypic variation was from 7.27% to 13.31%. Five of 26 QTLs identified in this study were co-localized with the previously cloned genes or previously identified QTLs related to Al tolerance or root growth/development. These results indicated that landraces are importance sources for Al tolerance in rice and the mapping results could provide important information to breed Al tolerant rice cultivars through marker-assisted selection.